2018
DOI: 10.29252/jafm.11.04.28084
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations into the Origin of Tip Unsteadiness in a Transonic Compressor

Abstract: Three-dimensional numerical simulations are conducted to investigate the origin of flow unsteadiness and its associated unsteady flow phenomena in a transonic compressor rotor. The predicted results are compared with the available experimental data and a good agreement is achieved. The numerical monitoring results and further analyses of the flow field indicate that flow unsteadiness is detected in the passage with the operating condition approaching the stability limit, and the highest oscillating region is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Results showed that nonuniform tip clearance effectively reduced the leakage mass flow rate, leading to enhancement of overall performance of the transonic compressor. An et al (2018) analyzed the blade tip unsteadiness in a transonic compressor using NASA Rotor 35. The unsteady results indicated that the shock/tip leakage vortex interaction generated the tip leakage vortex breakdown and caused a U-type vortex, whose periodic migration along blade pressure surface led to blade loading variation and flow unsteadiness near blade tip region; the shock oscillation was observed as indication of flow unsteadiness.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that nonuniform tip clearance effectively reduced the leakage mass flow rate, leading to enhancement of overall performance of the transonic compressor. An et al (2018) analyzed the blade tip unsteadiness in a transonic compressor using NASA Rotor 35. The unsteady results indicated that the shock/tip leakage vortex interaction generated the tip leakage vortex breakdown and caused a U-type vortex, whose periodic migration along blade pressure surface led to blade loading variation and flow unsteadiness near blade tip region; the shock oscillation was observed as indication of flow unsteadiness.…”
Section: Introductionmentioning
confidence: 99%
“…The unsteady characteristics of clearance leakage flow may also cause compressor rotating stall, which will have a very adverse impact on compressor performance. At present, it is considered that the self-induced unsteadiness (Du et al 2010), vortex splitting and vortex breakdown (Liu et al 2016b;An et al 2018;Wu et al 2019), are the main reasons of stall initiation mechanism, and a lot of work has been done (Vo et al 2008).…”
Section: Introductionmentioning
confidence: 99%